2009
DOI: 10.1007/s00394-009-0062-6
|View full text |Cite
|
Sign up to set email alerts
|

Promotive effects of resistant maltodextrin on apparent absorption of calcium, magnesium, iron and zinc in rats

Abstract: BackgroundIt has been reported that low-viscous and fermentable dietary fiber and nondigestible oligosaccharides enhance mineral absorption. Resistant maltodextrin, nonviscous, fermentable and soluble source of dietary fiber, has several physiological functions. However, influence of resistant maltodextrin on mineral absorption is unclear.Aim of the studyWe conducted balance studies in rats to investigate effects of resistant maltodextrin and hydrogenated resistant maltodextrin on apparent mineral absorption.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 17 publications
1
29
1
Order By: Relevance
“…Resistant maltodextrin (RMD) is a non-viscous soluble dietary fiber having various physiological effects, which were demonstrated by in-vitro, in-vivo and clinical experiments (20)(21)(22)(23). It has been reported that the continuous ingestion of 15-30 g/d of RMD significantly improves glucose and lipid metabolism (24)(25)(26).…”
Section: Improvement Effect Of Resistant Maltodextrin In Humans Withmentioning
confidence: 99%
“…Resistant maltodextrin (RMD) is a non-viscous soluble dietary fiber having various physiological effects, which were demonstrated by in-vitro, in-vivo and clinical experiments (20)(21)(22)(23). It has been reported that the continuous ingestion of 15-30 g/d of RMD significantly improves glucose and lipid metabolism (24)(25)(26).…”
Section: Improvement Effect Of Resistant Maltodextrin In Humans Withmentioning
confidence: 99%
“…In addition, our previous study showed that caecal weight was larger in rats fed a combination of dairy product fermented by lactobacilli and GOS than in rats fed the dairy product fermented by lactobacilli or GOS alone, suggesting that dairy product fermented by lactobacilli and GOS additively or synergistically increased caecal fermentation. In the present study, we observed increased caecal weight in the PPI + YG group, indicating increased caecal fermentation [31,32], which could be implicated in the increased calcium absorption. The potential positive effects of low-digestible carbohydrates on calcium absorption in large intestine can be explained by the following mechanisms [33].…”
Section: Discussionmentioning
confidence: 73%
“…Intestinal regularity is typically influenced by DF, and studies have shown that RMD increases stool frequency and volume in humans [22]. Furthermore, it has been reported that RMD is fermented by the intestinal bacterial flora, including bifidobacteria, resulting in an increase in the types and number of bacteria in the intestinal flora [20, 2327]. Fermentation by gut bacteria leads to short-chain fatty acid (SCFA) production, mainly: acetate, propionate and butyrate.…”
Section: Introductionmentioning
confidence: 99%